Study on treatment of radioactive liquid waste from uranium ore processing by the use of nano oxide ferromagnetic - Vuong , Huu Anh; Nguyen , Van Chinh; Nguyen , Ba Tien; Doan Thi , Thu Hien; Luu , Cao Nguyen (Nuclear Science and Technology, 2015)
Nano oxide ferromagnetic Fe3O4 KT wich was produced by the Military Institute of Science and Technology ​​were used to adsorbed heavy metal elements in liquid waste. In this report, the nano oxide ferromagnetic Fe3O4 KT with the particle size of 80-100nm and the specific surface area ​​of 50-70m2/g was applied to study the adsorption of radioactive elements in the liquid waste of uranium ores processing. The effective parameters on adsorption process included temperature, stirring rate, stirring time, the pH value of the solution, the initial concentration of uranium in solution were investigated. The results showed that the maximum adsorption capacity for uranium of the nano Fe3O4 KT was 53.5 mgU/g with conditions such as: room temperature, stirring speed 120 rounds/minute, the pH value of solution was 8, stirring time about 2 hours . From the results obtained, nano Fe3O4 KT was tested to treatment real liquid waste of uranium ore processing after removing almost heavy metals and a part of radioactive elements by preliminary precipitation at pH 8. The results were analyzed on the ICP-MS and α, β total activity equipment, the solution concentration after treatment suitable for Vietnamese Technical Regulation on industrial wastewater QCVN 40: 2011 (concentrations of heavy metals; total activity of α and β).